Shared Surgical Decision Making in the Era of COVID-19: Lessons From Hurricane Katrina. (February 2021) - Erbele, Isaac D.; Arriaga, Moisés A.; Nuss, Daniel W.
The COVID-19 pandemic has challenged every surgical discipline. Lessons learned from Hurricane Katrina have informed our department's management of the current crisis. That experience impressed upon us a profound appreciation for shared decision making in the face of scarce resources, an evolving clinical context, and potential harm to patients and health care workers. To that end, we have formed a Resource Utilization Committee to prospectively review all nonemergent surgical cases during the current crisis. This has allowed "state-of-the-pandemic" otolaryngologic care in a real-time, collaborative, and high-information setting. In addition, to protect our patients and health care workers, it has influenced our institution's thoughtful application of COVID testing and the use of personal protective equipment.